THE LEAN METHODOLOGY APPLIED TO HEALTHCARE INSTITUTIONS: A SYSTEMATIC LITERATURE REVIEW (CIPEEX, 2022)
SINCE HEALTH SYSTEMS HAVE DUE COMPLEXITY, BOTH IN PROCESSES AND IN MANAGEMENT, LEANHEALTHCARE, DERIVED FROM THE LEAN PHILOSOPHY, IMPROVES PROCESSES IN THEIR ENTIRETY, WITH A VIEWTO A GRADUAL RISE IN QUALITY THAT GENERATE BENEFITS IN THE CARE PROVIDED. THE OBJECTIVE OF THESTUDY WAS TO VERIFY, THROUGH ORIGINAL STUDIES, THE APPLICABILITY OF THE LEAN HEALTHCAREMETHODOLOGY AS A WAY OF IMPROVING PROCESSES IN HEALTH INSTITUTIONS, IDENTIFYING POSTIMPLEMENTATION CHANGES. THROUGH A QUALITATIVE AND DESCRIPTIVE SYSTEMATIC LITERATURE REVIEWCONDUCTED USING THE PRISMA METHODOLOGY, WITH RESEARCH CARRIED OUT IN THE CAPES, AND INTHE PUBMED AND SCIELO DATABASES. THE INITIAL SEARCH HAD 77 STUDIES, AFTER APPLYING THEINCLUSION CRITERIA BEING NATIONAL (PORTUGUESE), INTERNATIONAL (ENGLISH) STUDIES AND STUDIES THATCONTAIN THE WORD LEAN IN THE TITLE, 27 OF THE STUDIES DID NOT MEET THESE CRITERIA, THEN WAS APPLIEDTHOSE OF EXCLUSION THAT WERE STUDIES NOT FOUND IN FULL, DUPLICATE STUDIES, STUDIES THAT DO NOTHAVE LEAN HEALTHCARE AS A FOCUS AND NON-ORIGINAL STUDIES, WHERE 42 STUDIES MET THESE CRITERIA,REACHING A TOTAL OF 8 SELECTED STUDIES. EVEN SO, THE SEARCH STRATEGY WAS CARRIED OUT IN THEREFERENCES OF THE SELECTED STUDIES BASED ON THE INCLUSION AND EXCLUSION CRITERIA, WHERE IT WASPOSSIBLE TO SELECT FIVE STUDIES IN WHICH THE FINAL DATABASE WAS CONSTITUTED IN 13 STUDIES, WITHOUTTIME LIMITATION SO THERE WAS NO ELIMINATION OF STUDIES THAT THEY BELIEVE TO BE IMPORTANT FOR THEDEVELOPMENT OF THE RESEARCH. THE STUDIES CONVERGE IN THEIR OBJECTIVES IN UNDERSTANDING ANDIMPROVING OPERATIONAL PROCESSES USING THE IMPLEMENTATION OF LEAN METHODOLOGY IN HEALTHSYSTEMS. THE MAIN CONCLUSIONS IN THESE STUDIES WERE SIGNIFICANT CHANGES IN THE SECTORSCOVERED, OF WHICH 12 WERE STUDIES FOCUSED ON THE PATIENT, WITH LEAD TIME REDUCTION ANDIMPROVEMENT IN ITS FLOW. IN ADDITION, IT OBTAINED A REDUCTION IN QUEUES AND A FOCUS ON CARE ANDMANAGEMENT PROCESSES, INCREASING THE SATISFACTION OF THE TEAM, BEING POSSIBLE TO NOTE THATLEAN AFFECTS EMPLOYEES MAINLY IN A POSITIVE WAY. FROM THE 13 STUDIES ANALYZED, IT WAS VERIFIEDTHE AUTHORS' SEARCH TO BRING IMPROVEMENTS AND CHANGES THROUGH THE LEAN METHOD WITHIN THESCOPE OF HEALTH WITH A FOCUS ON PATIENTS, EMPLOYEES AND PROCESS FLOW. IN THIS WAY, IT WASPOSSIBLE TO VERIFY THAT, WITH THE LEAN HEALTHCARE IMPLEMENTATION, THERE WAS A SIGNIFICANTINFLUENCE. IN ADDITION TO VERIFYING THAT THERE ARE LIMITATIONS IN THE STUDIES THAT ARE OF A SINGLECASE, LIMITATION OF RESOURCES USED FOR THEIR IMPLEMENTATION, AND FOR BEING A RELATIVELY NEWPHILOSOPHY. THE STUDIES ALSO SUGGEST A DEEPENING OF RESEARCH IN ITS EXPANSION OF DATA AND IN OTHER AREAS SUCH AS ADMINISTRATION AND INVOLVING CONTINUOUS IMPROVEMENT PROJECTS IN FAVOR OF LEAN PRODUCTION, IN ADDITION TO HAVING MORE EXPRESSIVE SAMPLES.